Effects of butanol blending on spray auto-ignition of gasoline surrogate fuels. (15th January 2020) - Fan, Yunchu; Duan, Yaozong; Liu, Wang; Han, Dong
Abstract: Effects of butanol isomers on spray auto-ignition of two gasoline surrogate fuels, primary reference fuels (PRF) and toluene primary reference fuels (TPRF), were experimentally studied on a constant volume combustion facility. Combustion pressures, heat release rates, ignition delay (ID) and combustion delay (CD) times were compared and discussed in the context of changed fuel compositions and ambient temperatures. Experimental results revealed that butanol addition inhibits the spray auto-ignition propensity of PRF80 or TPRF80 surrogate fuels, which have the same research octane number of 80, and extends both the ID and CD times. The four butanol isomers extend the ID times of gasoline surrogates in an order of i-butanol > s-butanol ~ n-butanol > t-butanol, and the shortest ID times of the t-butanol/gasoline surrogate blends are attributed to their earliest first-stage heat release. Generally, the CD extension effects of the four butanol isomers are ranked as i-butanol > t-butanol ~ s-butanol > n-butanol, but the effects of s-butanol and t-butanol are slightly sensitive to the gasoline surrogate composition and ambient temperature.